Dinamisasi Bahasa Pascapandemi Pada Whatsapp Grup Siswa Kelas Viii Dan Implikasinya Dengan Pembelajaran Teks Persuasi - Rachmawati, Titi; Rosalina, Sinta; Supriadi, Oding (Peneliti.net, 2023)
The study was conducted to analyse the language changes that occur inwhatsapp groups of class VIII student at SMPN 2 Cibitung in the post -pandemic period as well as their implication of persuasive text teaching mediain the from of posters. The research method used in this research in descriptivequalitative method. The amount of data containing language changes inwhatsapp groups conversations of class VIII J student at SMPN 2 Cibitungthat the author has collected is 270 conversations containing languagechanges based on changes in phonology, morphology, and semantic. Of the270 conversation data in this study, 84 conversation data containingphonological changes were found, consisting of 10 word containing changeswith the addition of phonemes, 44 word containing changes with phonemechanges, and 67 word containing changes with phoneme removal. Furthermor,170 data countaining morphonological changes were found, consisting of 69word containing changes by affixation, 21 word countaining changes byreduplication, and 27 word countaining changes by abbreviation. The last, 107data countaining semantic changes were found, consisting of 29 wordcontaining connotation meaning and 85 word containing denatation meaning